EVALUATION OF THE EFFECTIVENESS OF SCHOOL MEAL PROGRAM ON NUTRITIONAL STATUS AND LEARNING CONCENTRATION OF ELEMENTARY SCHOOL STUDENTS - Syahruddin Mahmud; Masrifa Hidayani; Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2024)
This study aims to examine the effectiveness of the school meal program in improving the nutritional status and learning focus of primary school students. The research method implemented in this study is the literature study method. The results suggest that school meal programs can play an effective role in tackling the problem of undernutrition and obesity among school children by providing access to balanced and wholesome meals. In addition, the findings indicated the continuation of food quality and quantity as determining factors in improving students' nutritional status and academic performance. The conclusion of this study emphasizes the importance of collaboration between schools, government and parents in supporting school meal programs. Investing in school meal programs will not only contribute to the improvement of children's nutritional status but also to increased academic focus and performance, which in turn, prepares a better foundation for their physical and academic future